2018
DOI: 10.1002/joc.5791
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of El Niño–Southern Oscillation on South African temperatures during austral summer

Abstract: Using composite analysis, the timing and extent of El Niño-Southern Oscillation (ENSO) impacts on maximum (T max ) and minimum temperatures (T min ) during austral summer are investigated for South Africa over the period 1940-2016. Pearson correlation coefficients determined between temperature data at stations within regions indicate that temperature records are coherent. During austral summer, composite analysis exhibits positive T max /T min anomalies for El Niño years while negative anomalies are recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…The central interior (coinciding with our CSub region) experiences the strongest ENSO‐related temperature response, followed by the northern interior (coinciding with our NESA region); in contrast, the northeastern interior (coinciding with our ESA region) records the strongest temperature responses during La Niña events (Lakhraj‐Govender and Grab, 2018). It has also been identified that responses to ENSO events are usually most pronounced during austral summer (Nicholson and Kim, 1997; Mason, 2001; Lakhraj‐Govender and Grab, 2018). The SSTs generated in our study suggest a likeness to La Niña conditions following each of the four eruptions, which could contribute to the cooler temperatures over southern Africa.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The central interior (coinciding with our CSub region) experiences the strongest ENSO‐related temperature response, followed by the northern interior (coinciding with our NESA region); in contrast, the northeastern interior (coinciding with our ESA region) records the strongest temperature responses during La Niña events (Lakhraj‐Govender and Grab, 2018). It has also been identified that responses to ENSO events are usually most pronounced during austral summer (Nicholson and Kim, 1997; Mason, 2001; Lakhraj‐Govender and Grab, 2018). The SSTs generated in our study suggest a likeness to La Niña conditions following each of the four eruptions, which could contribute to the cooler temperatures over southern Africa.…”
Section: Discussionmentioning
confidence: 79%
“…Our findings thus demonstrate strongly contrasting temperature responses to volcanic forcing between the more continental climatic/summer rainfall regions (CSub, NESA), and the Mediterranean/subtropical climates of the winter/all year rainfall regions (i.e., SWC/ECC respectively). Strong El Niño Southern Oscillation (ENSO) phases tend to have more significant temperature effects over the interior than coastal regions of southern Africa, with the CSub and NESA regions most strongly impacted by the El Niño anomaly, and result in positive temperature departures (Lakhraj‐Govender and Grab, 2018). The somewhat weaker responses along coastal regions (ECC and SWC) may also be due to oceanic temperature‐regulating effects, particularly the cool Benguela current that borders the SWC (Philippon et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A range of studies have shown that ENSO events significantly impact global weather and climatic variables [9][10][11][12][13][14][15][16][17][18]. For instance, Rishma and Katpatal [17] reported that the average rainfall during El Niño years was less than it was during La Niña and normal years in central India.…”
Section: Introductionmentioning
confidence: 99%
“…Since ENSO signals have strong teleconnection impacts on climate variables, which can substantially regulate crop production in some regions of the world [14,16,[23][24][25][26][27][28]. As each crop requires a cardinal temperature and a specific amount of rainfall for its proper growth and development.…”
Section: Introductionmentioning
confidence: 99%